Unveiling research hotspots: a bibliometric study on macrophages in musculoskeletal diseases - Yue, Yaohang; Cao, Siyang; Cao, Fuyang; Wei, Yihao; Li, Aikang; Wang, Deli; Liu, Peng; Zeng, Hui; Lin, Jianjing (Frontiers in Immunology, 2025)
Research on the role of macrophages in musculoskeletal (MSK) diseases has significantly increased in recent years. However, a thorough evaluation of the developmental trajectory of this field, including the contributions of prominent authors and primary research themes, remains insufficient. Furthermore, the identification of emerging research hotspots requires more detailed exploration. This study collated articles and reviews addressing “macrophages in MSK diseases” published between 2004 and 2023, with all data extracted from the Web of Science database. The collected data were analyzed using a variety of bibliometric and visualization tools, such as VOSviewer, CiteSpace, GraphPad Prism, and R packages. Results indicate that China and the United States are the leading contributors in this research domain. Among the many academic institutions involved, Shanghai Jiao Tong University and the University of California stand out as the most productive. The journal “Frontiers in Immunology” had the highest publication output on this topic. The five most frequently explored research domains include Immunology, Rheumatology, Pharmacology and Pharmacy, Cell Biology, and Biochemistry and Molecular Biology. These results offer a comprehensive overview of the current state of research in this field and provide meaningful insights for guiding future studies.